Edusin project (educa-salud: research and move safely): An intervention program on myths in physical activity and health - Cendrero-Rodríguez, B.; Ruiz-Tendero, G. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The present work, called project EDUSIN has as main objective to promote in educational environments, a culture of physical activity and health based on knowledge, through the active participation of the students themselves. For this, an intervention was carried out in an educational center in Madrid (Carabanchel), in which 65 students of 4th ESO participated. The level of knowledge of the students about myths related to health and physical exercise was assessed through the MAFYS Questionnaire. Subsequently, the students made posters of the different myths with the aim of raising the awareness of the educational community of false beliefs. On the one hand, the quality of the intervention carried out was assessed and, on the other hand, the scope of the dissemination. The results showed that the level of knowledge of the students is medium (47.2% of correct answers), the quality of the evaluation of the project has been remarkable (global average = 8.53), as well as the reach of the dissemination reaching 100% of the respondents.